Representing Poverty and Precarity in a Postcolonial World - Schmidt-Haberkamp, Barbara; Gymnich, Marion; Schneider, Klaus P. (Cross/Cultures, 2021)
The contributions to this volume address conceptualisations of poverty and precarity from the perspective of literary and cultural studies as well as linguistics and investigate the ethics and aesthetic of representing poverty and precarity across the postcolonial world.; Readership: All interested in poverty and precarity studies in literary and cultural studies as well as linguistics, specifically in representations impacting affective and ethical responses to disenfranchised groups and precarious subjects.